simplify this question
yh vala agar sahi answer diya to agli bar Points bada ke question puchunga ok
Attachments:
![](https://hi-static.z-dn.net/files/d64/28d69e827610c43a0d22ec8380af07ec.jpg)
Answers
Answered by
1
Answer:
(x+y)(y+z)(z+x)
Step-by-step explanation:
Taking first Numerator
N=(x²-y²)³+(y²-z²)³+(z²-x²)³
Here (x²-y²)+(y²-z²)+(z²-x²)=0
so N=(x²-y²)³+(y²-z²)³+(z²-x²)³=3(x²-y²)(y²-z²)(z²-x²)----------------(1)
similarly Denominator
D=(y-z)³+(z-x)³+(x-y)³=3(y-z)(z-x)(x-y)
So fraction=N/D=3(x²-y²)(y²-z²)(z²-x²)/3(y-z)(z-x)(x-y)
=(x+y)(y+z)(z+x)
Anonymous:
ok dear thanks
Similar questions